Effects of `posture length` on joint power in cycling - Hayot, C.; Decatoire, A.; Bernard, J.; Monnet, T.; Lacouture, P. (Procedia Engineering, 2012)
Problems of posture in cycling are closely related to a badly adjusted saddle. Many of these problems can be prevented if the bicycle is correctly adjusted. In the search for an optimum posture of the cyclist, a balance should be found to both prevent injuries and enhance performance. If the influence of bicycle `posture height` on generation of muscular power is largely investigated, little attention is carried out about the effects of `posture length` on the cyclist neuromuscular strategy. The purpose of the present study is to compare joint powers for different configurations of the cyclist `posture length`. Fourteen competitive cyclists and triathletes (28.2 ± 7.5 years) perform 3-min trials on a stationary cycloergometer at four different `posture lengths` (preferred, backward, intermediate, forward) each separated by one minute of rest. The cyclists exercise an external power of 3.8 ± 0.1 W/kg and pedaling cadence is controlled at 90 ± 5 rpm for all trials. Three-dimensional external forces and moments were measured at each pedal using six components force sensors. Using pedal forces and lower limb three-dimensional kinematics, joint powers are calculated at the ankle, knee and hip joints using an inverse dynamics procedure and normalized to the subject body mass. The results of pedal and joint powers output show that preferred and forward posture lead to develop larger knee power than backward posture. The latter requires to develop supplementary joint power at the hips that compensate joint power deficiency at the knees.